Model 25 spectrophotometer, vacuum control, and printer (1970)
Beckman's foray into ultraviolet spectroscopy began in 1940, when the company (then called National Technical Laboratories) produced the DU prototype. The double-beam Model 25 was introduced in the early 1970s.
Keywords: Ultraviolet spectroscopy; Scientific apparatus and instruments; Spectrophotometer; Beckman Instruments, Inc.